Influence of Water-Cement Ratio and Type of Mixing Water on the Early Hydration Performance of Calcium Sulphoaluminate (CSA) Cement - Chuanlin Wang; Meimei Song (Advances in Materials Science and Engineering)
The present work studies the influence of water-cement ratio and types of mixing water on the hydration process and microstructure of calcium sulphoaluminate (CSA) cement. Experimental tests on the setting time, physical properties, compressive strength, chemical shrinkage, X-ray diffraction (XRD), and scanning electron microscopy (SEM) of CSA cement paste were carried out. The XRD analysis confirmed that the main hydration product is ettringite in both freshwater and seawater mixed CSA cement with different w/c ratios. The SEM analysis and physical properties test show that both low w/c ratio and seawater can improve the microstructure of CSA cement. The test results also find out that the high w/c ratio can accelerate the hydration process, extend the setting time, lower the compressive strength, and increase the chemical shrinkage of CSA cement, and the seawater presents a similar influence except for the mechanical property. The seawater increases the compressive strength of CSA cement in the early stage of hydration but will increase the microcracks at the later hydration stage of CSA cement and reduce its mechanical properties.